2016
DOI: 10.1002/esp.4072
|View full text |Cite
|
Sign up to set email alerts
|

Floodplain downed wood volumes: a comparison across three biomes

Abstract: Downed large wood (LW) in floodplains provides habitat and nutrients for diverse organisms, influences hydraulics and sedimentation during overbank flows, and affects channel form and lateral migration. Very few studies, however, have quantified LW volumes in floodplains that are unaltered by human disturbance. We compare LW volumes in relatively unaltered floodplains of semiarid boreal lowland, subtropical lowland, and semiarid temperate mountain rivers in the United States. Average volumes of downed LW are 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 88 publications
0
50
2
Order By: Relevance
“…The majority of LW is recruited here directly from the active valley floor by tree throws, which most likely happens only during high-magnitude flood events similar to the 2000 event. Although some previous studies suggested slow decay rates of wood in semi-arid conditions [17,18], we observed relatively fast decay processes in the Sfakiano most likely due to biotic agents (wood-destroying insects). Therefore we were not able to successfully apply cross-dating methods to estimate residence time or the year of LW recruitment in this ephemeral stream.…”
Section: Total Large Wood Loadings and Wood Recruitmentcontrasting
confidence: 90%
“…The majority of LW is recruited here directly from the active valley floor by tree throws, which most likely happens only during high-magnitude flood events similar to the 2000 event. Although some previous studies suggested slow decay rates of wood in semi-arid conditions [17,18], we observed relatively fast decay processes in the Sfakiano most likely due to biotic agents (wood-destroying insects). Therefore we were not able to successfully apply cross-dating methods to estimate residence time or the year of LW recruitment in this ephemeral stream.…”
Section: Total Large Wood Loadings and Wood Recruitmentcontrasting
confidence: 90%
“…However, a similar experiment presented by Aponte et al [8] had an almost identical mean volume of 68 m 3 ha −1 in its experimental plots, while the long unburnt plots presented were much higher at 96 m 3 ha −1 . Northern American boreal (42.3 m 3 ha −1 ) and subtropical (50.4 m 3 ha −1 ) floodplains are lower than our presented value, while temperate floodplains are considerably higher (116.3 m 3 ha −1 ) [41].…”
Section: Discussioncontrasting
confidence: 75%
“…In summary, low wood abundance in the studied reaches were dictated mainly by the presence of sparse riparian corridors as recruitment areas of LW, as well as by the specifics of the decay of local coniferous trees and the flashy hydrological regime of the streams draining this semiarid Mediterranean environment. The limited production of biomass in semiarid climatic zones is perceived to be imprinted in low‐frequency recruitment of wood pieces rather than small sizes, which leads to low LW volumes in these channels (Galia, Škarpich, et al, ; Lininger et al, ; Wohl et al, ). Our quantification of living tree biomass along the stream courses confirmed this assumption, as the mean basal area of all trees in the riparian corridor was equal to 17.4 m 2 /ha.…”
Section: Discussionmentioning
confidence: 99%